A polymorphism in the MSH3 mismatch repair gene is associated with the levels of somatic instability of the expanded CTG repeat in the blood DNA of myotonic dystrophy type 1 patients - Morales Montero, Fernando (2016)
Somatic mosaicism of the expanded CTG repeat in myotonic dystrophy type 1 is age-dependent, tissuespecific and expansion-biased, contributing toward the tissue-specificity and progressive nature of the symptoms. Previously, using regression modelling of repeat instability we showed that variation in the rate of somatic expansion in blood DNA contributes toward variation in age of onset, directly implicating somatic expansion in the disease pathway. Here, we confirm these results using a larger more genetically homogenous Costa Rican DM1 cohort (p < 0.001). Interestingly, we also provide evidence that supports subtle sex-dependent differences in repeat length-dependent age at onset and somatic mutational dynamics. Previously, we demonstrated that variation in the rate of somatic expansion was a heritable quantitative trait. Given the important role that DNA mismatch repair genes play in mediating expansions in mouse models, we tested for modifier gene effects with 13 DNA mismatch gene polymorphisms (one each in MSH2, PMS2, MSH6 and MLH1; and nine in MSH3). After correcting for allele length and age effects, we identified three polymorphisms in MSH3 that were associated with variation in somatic instability: Rs26279 (p = 0.003); Rs1677658 (p = 0.009); and Rs10168 (p = 0.031). However, only the association with Rs26279 remained significant after multiple testing correction. Although we revealed a statistically significant association between Rs26279 and somatic instability, we did not detect an association with the age at onset. Individuals with the A/A genotype for Rs26279 tended to show a greater propensity to expand the CTG repeat than other genotypes. Interestingly, this SNP results in an amino acid change in the critical ATPase domain of MSH3 and is potentially functionally dimorphic. These data suggest that MSH3 is a key player in generating somatic variation in DM1 patients and further highlight MSH3 as a potential therapeutic target.